A novel bipolar phosphorescent host for highly efficient deep-red OLEDs at a wide luminance range of 1000–10 000 cd m−21. Issue 63 (14th August 2015) - Feng, Yansong; Li, Ping; Zhuang, Xuming; Ye, Kaiqi; Peng, Tai; Liu, Yu; Wang, Yue
<x xml:space="preserve">Abstract</x> A novel bipolar phosphorescent host FPYPCA with narrow Eg as well as high T1 realizes the most efficient deep-red PhOLED (R1–15), which maintains very high EQEs of >23% at rather high and wide luminance range of 1000–10 000 cd m−2.